2018
DOI: 10.1371/journal.pone.0208303
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in men and women with cardiovascular diseases and its association with the use of health care services - Results from the population-based GEDA2014/2015-EHIS survey in Germany

Abstract: BackgroundHealth literacy (HL), defined as the ability to access, understand, appraise and apply health information, offers a promising approach to reduce the development of cardiovascular diseases (CVD) and to improve the management of CVD in populations.DesignWe used data from nationwide cross-sectional German Health Update (GEDA2014/2015-EHIS) survey. 13,577 adults ≥ 40 years completed a comprehensive standardized paper or online questionnaire including the short form of the European Health Literacy Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 60 publications
0
28
1
7
Order By: Relevance
“…Conversely, only four studies were conducted in the East 10 , 86 , 87 , and two studies referred to refugees from non-EU countries 29 , 88 . A consistent heterogeneity was observed among the tools used to assess HL: the most frequently used tools were the Newest Vital Sign, applied in 21 studies 42 , 43 , 45 , 47 , 52 , 55 58 , 63 , 67 , 73 , 77 , 79 , 82 , 84 , followed by the European Health Literacy Survey Questionnaire with 16 items ( n = 15) 26 , 27 , 33 , 34 , 38 , 50 , 60 , 71 , 75 , 78 , 83 , 86 and the Rapid Estimate of Adult Literacy in Medicine ( n = 12) 30 , 31 , 40 – 42 , 47 49 , 73 , 76 . The European Health Literacy Survey Questionnaire with 47 items 38 , 43 , 55 , 62 , 63 , 78 , 84 , 87 and its longer version with 86 items 10 , 58 were used eleven and nine times each, respectively, followed by the Single Item Literacy Screener ( n = 8) 44 , 61 , 65 , 66 , 69 , 82 and the Medical Term Recognition Test ( n = 7) 56 , 64 , ...…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, only four studies were conducted in the East 10 , 86 , 87 , and two studies referred to refugees from non-EU countries 29 , 88 . A consistent heterogeneity was observed among the tools used to assess HL: the most frequently used tools were the Newest Vital Sign, applied in 21 studies 42 , 43 , 45 , 47 , 52 , 55 58 , 63 , 67 , 73 , 77 , 79 , 82 , 84 , followed by the European Health Literacy Survey Questionnaire with 16 items ( n = 15) 26 , 27 , 33 , 34 , 38 , 50 , 60 , 71 , 75 , 78 , 83 , 86 and the Rapid Estimate of Adult Literacy in Medicine ( n = 12) 30 , 31 , 40 – 42 , 47 49 , 73 , 76 . The European Health Literacy Survey Questionnaire with 47 items 38 , 43 , 55 , 62 , 63 , 78 , 84 , 87 and its longer version with 86 items 10 , 58 were used eleven and nine times each, respectively, followed by the Single Item Literacy Screener ( n = 8) 44 , 61 , 65 , 66 , 69 , 82 and the Medical Term Recognition Test ( n = 7) 56 , 64 , ...…”
Section: Resultsmentioning
confidence: 93%
“…The other tools were used in a limited number of studies, from one to three each (Table 1 ). Most studies investigated HL using self-reported comprehension items 26 , 27 , 30 , 33 , 34 , 36 , 38 , 44 , 48 50 , 54 , 55 , 58 , 60 , 61 , 67 , 68 , 70 72 , 74 76 , 78 , 81 , 83 , 85 , 86 ( n = 38); 29 studies used reading or numeracy comprehension items 35 , 37 , 39 – 43 , 45 47 , 51 , 52 , 55 58 , 63 , 67 , 73 , 77 , 79 , 80 , 82 , 84 ; 23 studies used word recognition items 28 32 , 58 , 59 , 62 , 65 , 66 , 79 , 82 ; and nine studies used a mixed method 10 , 58 . Sixty-six studies quantified low HL in the general population 10 , 26 , 29 , 31 34 , 36 , 39 , 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lediglich zu einzelnen Erkrankungen wie bspw. zur Gesundheitskompetenz bei Herz-Kreislauf-und Krebserkrankungen existieren hier erste explorative Studien [11][12][13]. International, v. a. in den USA, besteht eine langjährige Forschungstradition zur Gesundheitskompetenz von MmcE [14].…”
Section: Introductionunclassified
“…Die Zahl dieser Studien ist in Deutschland jedoch noch gering. Auch Auswertungen für einzelne Bevölkerungsgruppen liegen nur vereinzelt vor [11,20]. Wichtig ist bei chronischer Krankheit zudem, die Dauer und die Anzahl der Krankheiten zu berücksichtigen.…”
Section: Introductionunclassified